Deteksi Sederhana Boraks dan Formalin pada Makanan Jajanan Anak dengan Bunga Terompet Ungu (Ruellia Tuberosa) - Rini Tri Hastuti; Youstiana Dwi Rusita (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Abstract Background: Borax and Formalin are often misused by naughty producers as additional preservatives in children's snacks such as cilok, meatballs, noodles and other foods. BPOM data shows that throughout 2012, the incidence of poisoning due to consuming food occupied the highest position, namely 66.7%, one of the causes of food poisoning was the presence of chemical contamination in children's snack foods, such as borax and formalin. The accumulation of these substances in the body can have a negative impact on health. Purple trumpet flower is a simple detection material to find out the presence of borax and formalin in food. The aim of community service is to increase knowledge in mothers of school-age children, how to detect simple borax and formalin in children's snacks with purple trumpet flowers. Methods: The method by means of detection training is how to detect simple borax and formalin in children's snacks with purple trumpet flowers. Results: From the results of community service, that mothers with 90% of school-age children can do a simple way of detecting borax and formalin in children's snacks with purple trumpet flowers. Conclutions: that mothers of school-age children can do a simple way of detecting borax and formalin in children's snacks with purple trumpet flowers.